(untitled) (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2021)
This paper presents a qualitative and quantitative study with experimental fluid and electrodynamics activities in a Science Fair held in the State School of Elementary and High School Teacher Filomena Quitiba, located in the city of Piúma-ES, Brazil. The activities were developed based on the Diagram V, proposed by David Bob Gowin in 1977. To infuse the ideas of this heuristic at the science fair, two Pedagogical Workshops were offered to high school students who developed ten activities with Diagram V as the guiding procedure. Data were collected and evaluated throughout the process, which, in the end, evidenced the successful infusion of Gowin’s heuristic, as it provided praxis in the construction of knowledge. Therefore, the results reveal that the students understood the importance of the dynamics of Diagram V as a reference instrument for the experiments developed for the Science Fair.